2016
DOI: 10.3389/fpsyg.2016.01423
|View full text |Cite
|
Sign up to set email alerts
|

Rational Emotive Behavior Therapy (REBT), Irrational and Rational Beliefs, and the Mental Health of Athletes

Abstract: In this article Rational Emotive Behavior Therapy (REBT) is proposed as a potentially important framework for the understanding and promotion of mental health in athletes. Cognitive-behavioral approaches predominate in the provision of sport psychology, and often form the backbone of psychological skills training for performance enhancement and maintenance. But far from being solely performance-focused, the cognitive-behavioral approach to sport psychology can restore, promote, and maintain mental health. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
200
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(220 citation statements)
references
References 135 publications
6
200
2
12
Order By: Relevance
“…In line with the notion that irrational beliefs should lead to unconstructive behaviours (Ellis, 1957), researchers have explored whether irrational beliefs are harmful to performance across a variety of settings (for a review, see Turner, 2016). Surprisingly, we were unable to identify any research that had explored associations between irrational beliefs and academic performance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In line with the notion that irrational beliefs should lead to unconstructive behaviours (Ellis, 1957), researchers have explored whether irrational beliefs are harmful to performance across a variety of settings (for a review, see Turner, 2016). Surprisingly, we were unable to identify any research that had explored associations between irrational beliefs and academic performance.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the extant research has not sufficiently examined the relationships between irrational beliefs and academic performance. It has been suggested that some level of irrational thinking could be helpful to performance in some acute circumstances (Turner, 2016;Turner & Barker, 2014). Irrational beliefs could suggest to the individual that more effort is required (to avoid failure) leading to some adaptive behaviours (e.g., increased study time).…”
Section: Introductionmentioning
confidence: 99%
“…In sport settings, irrational beliefs have been identified as important for the experience of anxiety (Turner & Barker, 2013), self-acceptance (Cunningham & Turner, 2016), burnout (Turner & Moore, 2016), resilience (Deen, Turner, & Wong, 2017), psychological distress (Turner, Carrington, & Miller, 2017), and task performance (Wood, Turner, Barker, & Higgins, 2017). Research in nonsport settings also reveals that irrational beliefs are associated with an array of emotional and behavioural malfunctioning (Visla, Fluckiger, Holtforth, & David, 2016) that could also afflict athletes (Turner, 2016). To advance research on irrational beliefs in athletic settings, it is important for researchers to develop valid and reliable measures.…”
Section: Introductionmentioning
confidence: 99%
“…and pragmatically) offers a pro-active approach that facilitates psychological health and goal 130 achievement (Turner, 2016). Furthermore, the use of REBT has been reported across various 131 performance settings such as, sport (e.g., Turner & Barker, 2014), education, and business…”
mentioning
confidence: 99%